Inovasi Disdukcapil dalam Memberdayakan Penyandang Disabilitas Melalui Program Pelayanan Dokumen Langsung Antar Kerjasama Disabilitas (PAK DOLA KADIS) di Kota Samarinda. - Hasugian, Marlinang Ruth Debora; Alaydrus, Anwar; Budiman, Budiman (Jurnal Ilmu Pemerintahan, 2023)
This research using a qualitative descriptive method and was conducted at the Population and Civil Registration Office of Samarinda City. The aim of this research is to analyze the Disdukcapil Innovation in Empowering Persons with Disabilities through the Direct Document Service Program in collaboration with Disabilities (Pak Dola Kadis) by measuring its success through the innovation characteristics indicators proposed by Rogers, which are Relative Advantage, Compatibility, Complexity, Trialability, Observability, as well as conducting an analysis of the inhibiting and supporting factors in the implementation of the innovation. The research results that Pak Dola Kadis is a successful innovation significant advantage. The formation of Pak Dola Kadis is highly compatible with the needs of the public and courier who do not have employment or income. There is a level of complexity, which includes difficulties in providing basic delivery material guidance, transportation difficulties, and the milage. Some members of the public may also have limited understanding of the conditions of courier with disabilities. The trialibility, indirectly conducted by Disdukcapil at the beginning of employment, has proven to be effective. The innovation is easily observable in its implementation by both Disdukcapil and the public general. Supportive factors for the innovation include the equipment provided to couriers, motivation from Disdukcapil, and the support from the Central Government and the public. On the other hand, inhibiting factors for the innovation include the condition of three-wheeled motorcycles, which are prone to more frequent breakdowns, and difficulties in navigating through poorly maintained roads.